Balancing on a slack line – Staffs’ experiences of talking about sexuality and sexual health with patients cared for in forensic psychiatry in Sweden - Lindskog, Anna; Lindroth, Malin; Holmgren, Kristina; Gunnarsson, Anna Birgitta (Frontiers in Psychiatry, 2024)
Sexuality is a central part of being human, however, talking about sexual health is generally avoided in forensic psychiatry. The aim of this qualitative study was to explore how healthcare professionals experience talking about sexuality and sexual health with patients cared for in forensic psychiatry. Individual interviews were conducted with eighteen healthcare professionals from ten different forensic psychiatry care units in Sweden. The interviews were semi-structured, and the data was analyzed with qualitative content analysis. The findings showed the overarching theme "Balancing on a slack line". The conversations the healthcare professionals have about sexuality and sexual health with patients in this setting are affected by forensic psychiatry's dual mission; to provide care and at the same time protect patients and society. These conversations can be about opening up for having responsive conversations, but also closing conversations since the field of sexuality and sexual health is fraught with norms and preconceptions. To be able to conduct these conversations can be a challenge since the professionals can experience uncertainty due to a lack of competence, indicating that knowledge and resources are needed to facilitate conversations. In conclusion, the study indicates that there is a lack of support and structure for performing conversations about sexuality and sexual health in forensic psychiatry care, and there is a need for increased knowledge among healthcare professionals. In order to support staff, the forensic psychiatry services need to acknowledge the national guidelines for sexual and reproductive health and rights and to develop and adapt the local guidelines.